In silico Exploration on The Potency of Basil (Ocimum basilicum) as an Anti-Aging Skin Agent - Wega Nasyita Amala; Raden Ahmad Zainul Aziz; Nur Rohmah; Hanun Najah Imtiyaz; Muhamad Dandi Iqbal Iskandar; Erlix Rakhmad Purnama (Pandawa Institute, 2023)
New and improved skin care products and procedures have been established by technological advances and scientific investigation. By increasing the skin's moisture, firmness, and elasticity, anti-aging skin care can enhance the skin's overall condition. The objective of this study was to examine the potential of basil's chemical compounds as an in silicoanti-aging agent. Exploration of online databases, scholarly articles from national and international journals, and analysis using docking software are selected as examples of data collection methods. Matrix metalloproteinase 1 (MMP1), with PDB code 966C, is one of the targeted proteins related to skin anti-aging. Ladanein, acacetin, luteolin, 5-hydroxy-7,4'-dimethoxyflavone and genkwanin are five basil compounds that are predicted to exhibit anti-aging agents based on the presence of the binding affinity score indicator and the similarity of the appropriate attachment sites compared to the native ligand used. The scores for the binding affinity of luteolin, ladanein, acacetin, 5-hydroxy-7,4'-dimethoxyflavone, and genkwanin are -10, -9.9, -9.9, -9.8, and -9.6 kcal/mol, respectively. At the attachment positions of five basil compounds, the interactions with ASN 180, LEU 181 and ALA 182 key amino acids, which are the attachment sites for the native ligands, were also formed.